Design And Development of a Web-Based Practicum Management Information System with QR Code Integration and Automated Notifications - Abdul Syakur; Clara Falisha Suardi; Devianty Lukman; Dimas Ari Wahyudi; Erma Hajrah; Erwin (Program Studi Teknik Komputer, 2025)
This study aims to design and develop a web-based Practicum Management Information System integrated with QR Code technology and automated notifications. The conventional practicum management process still relies on manual attendance recording and delayed information dissemination, resulting in inefficiency and administrative inaccuracies. This research applies the Research and Development (R&D) method using the Waterfall software development model. The stages include requirement analysis, system design, implementation, and testing. The system integrates QR Code for attendance validation and automated notification features via email to enhance communication efficiency. Black Box Testing and User Acceptance Testing (UAT) were conducted to evaluate system functionality and usability. The results show that the developed system improves attendance accuracy, accelerates administrative processes, and enhances real-time information delivery. The system contributes to increasing efficiency, transparency, and effectiveness in practicum management in higher education institutions.